Emergence of a New and Resurgent Woman in Assamese Fiction: A Study of Arupa Patangia Kalita’s “Mriganabhi” - Lt. C.K. Bhattacharyya, Dr. Sikhamani Sarma (International Journal of Advanced Science and Technology, 2020)
Women have received quite a variety of treatment in fictional works throughout India. While we see women in the guise of a self-confident entity in many a fictional works produced in modern India, in many other works we are presented with their misery and an irremediable plight in which they have to suffer immensely. Fiction in India’s North-East including Assam is no exception in this regard. It is evident from the novels written by the renowned Assamese novelist of our century, Arupa Patangia Kalita. A study of the novels written by Ms. Kalita in general and “Mriganabhi” (1987) in particular reveals that women continue to discover themselves at the receiving end mainly owing to age-old customs and traditions. The stiff codes and conventions of a patriarchal society always subjugate women and their rights, however educated and ‘empowered’ they might be. Yet, they do have the requisite psychological edge to come out of all the blues as exemplified by Sontara, a highly educated and employed woman, and the central character of the novel by Ms. Kalita. This paper ventures to explore the feats of the central woman character in the novel pitted against all adversaries and odds, on her way to emerge as a new and resurgent woman as the novel proceeds towards its end.